The evolution of the magmatic plumbing system associated with the Franklin Large Igneous Province (Victoria Island, Arctic Canada) - Hayes, Ben (2014)
This thesis is an investigation of the magmatic processes that operated in the plumbing system of the Franklin Large Igneous Province (LIP). The Franklin LIP (~723-716 Ma) extends >2500 km across northern Canada and is superbly exposed in the Minto Inlier of Victoria Island. The exposed plumbing system is dominated by sills, with subordinate fault-guided feeder dykes. Locally, sills are characterised by olivine-enriched bases, with overlying doleritic gabbros. One example is the Lower Pyramid Sill. This sill was investigated in detail using petrography, whole-rock chemistry and in-situ mineral chemistry. Petrological and geochemical observations, combined with inverse melt modelling show that the olivine-enriched layer formed by olivine slurry replenishment into a resident gabbroic mush. In contrast, the overlying gabbros formed by in-situ differentiation. Intervening clinopyroxene-rich cumulates formed by a metasomatic reaction between different pore melts. The study emphasises that both slurry emplacement and in-situ differentiation played a role in the formation of cumulate layering in this sill. Sections examined through the same sill along strike, collectively termed the Fort Collinson Sill Complex, reveal that the olivine slurry propagated >50 km downstream. Radiogenic and stable isotope data support this interpretation. The geochemical consequences of cumulate remobilisation and mixing in the sill complex are demonstrated, as well as quantified, using Fe=Mg modelling. Additionally, the effects of dolostone assimilation are considered, which can potentially affect phase equilibria. This thesis also investigates the Ni-Cu-PGE potential of the Franklin LIP by studying the Southern Feeder Dyke Complex. This dyke complex was fault-guided and brecciated dykes contain microdoleritic microxenoliths that are impregnated by sulphides. Immiscible sulphide liquids formed when the magma became sulphur saturated due to the ingestion of local sulphur-rich wallrock. This study demonstrates the importance of ...